Differences between meropenem and imipenem disk to detect carbapenemase in gram-negative bacilli using simplified carbapenem inactivation method. Issue 6 (June 2020) - Wan, Dapeng; Jing, Xiaopeng; Zhou, Huan; Min, Xiaochun; Zhang, Xing; Wu, Tingting; Liu, Rong; Zeng, Ji
Abstract: The spread of carbapenemase-producing Enterobacteriaceae (CPE) is a major threat to public health. In the present study, we compared the difference between meropenem and imipenem disk for detecting carbapenemase-producing gram-negative bacilli using simplified carbapenem inactivation method (sCIM). 106 Enterobacteriaceae, including 74 CPE, 17 Pseudomonas aeruginosa including 10 carbapenemase-producing isolates and 36 Acinetobacter baumannii including 20 carbapenem-resistant isolates preserved in our laboratory were tested. Based on sCIM method, the test bacteria were tested with both meropenem and imipenem disk, respectively. In Enterobacteriaceae, the usage of both meropenem and imipenem disk showed high concordance (99.1%). Meropenem disk cannot identify positive isolates among the 10 P. aeruginosa and 20 A. baumannii isolates due to low carbapenem hydrolytic ability of the carbapenemase produced by these strains. Thus, meropenem disk was found to be similar to imipenem disk, presenting high specificity and sensitivity in the detection of carbapenemase in Enterobacteriaceae, but it cannot be used for the detection of carbapenemase in P. aeruginosa and A. baumannii .